Synthetic biology : industrial and environmental applications - Schmidt, Markus, 1974- (Wiley-Blackwell ; Wiley-VCH, 2012)
This is the only book to focus on industrial and environmental applications of synthetic biology, covering 17 of the most promising uses in the areas of biofuel, bioremediation and biomaterials. The contributions are written by experts from academia, non-profit organizations and industry, outlining not only the scientific basics but also the economic, environmental and ethical impact of the new technologies.